Responsible Business in a Changing World New Management Approaches for Sustainable Development - Díaz Díaz, Belén; Capaldi, Nicholas; Idowu, Samuel O.; Schmidpeter, René (CSR, Sustainability, Ethics & Governance, 2020)
XVIII, 392 p. 56 illus., 35 illus. in color.